Pengaruh Media Audio-Visual terhadap Kemampuan Menyimak Cerita Siswa di SDI Sikumana 3 - Markus Sampe; Habibi Musa; Monica Bellandina Abolla (FKIP UNSULTRA, 2025)
Listening ability is one of the language skills that plays an important role in learning Indonesian in elementary schools. However, in practice, students' listening ability is still relatively low because learning tends to be conventional and does not utilize interesting learning media. This study aims to determine the effect of the use of audio-visual media on students' listening ability in SDI Sikumana 3. This study uses a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class that was given treatment using audio-visual media and the control class that used conventional learning methods. Data collection techniques were carried out through story listening ability tests in the form of multiple choices and short descriptions. Data were analyzed using descriptive and inferential statistical tests, including normality tests, homogeneity tests, and hypothesis tests using t-tests. The results showed that the average value of students' listening ability in the experimental class was higher than that of the control class. The results of the t-test showed that the significance value was less than 0.05, so it can be concluded that there is a significant effect of the use of audio-visual media on students' listening ability in stories. Thus, audio-visual media can be used as an effective alternative learning medium to improve students' listening skills in Indonesian language lessons in elementary schools.